Disruption, control and coping: responses of and to the person with dementia in hospital - Porock, Davina; Clissett, Philip; Harwood, Rowan H.; Gladman, John R.F. (Cambridge University Press, 2015)
This qualitative study aimed to gain insight into the experience of hospitalisation from the perspectives of the older person with dementia, their family care-giver and other patients sharing the ward (co-patients). Non-participant observation of care on 11 acute hospital wards was supplemented by 39 semi-structured interviews with 35 family care-givers and four co-patients following discharge. Constant comparative analysis produced the core problem facing all those involved: disruption from normal routine meaning that the experience of hospitalisation was disrupted by the presence and behaviour of the person with dementia. Disruption adversely affected the person with dementia, triggering constructive, disengaged, distressed and neutral behaviours. Using Kitwood's model of person-centred care, these behaviours were interpreted as attempts by the person with dementia at gaining a sense of control over the unfamiliar environment and experience. Family care-givers' lives and experiences both inside and outside the hospital were disrupted by the hospitalisation. They too attempted to gain a sense of control over the experience and to give a sense of control to the patient, co-patients and staff. Co-patients experienced disruption from sharing space with the person with dementia and were left feeling vulnerable and sometimes afraid. They too attempted to gain a sense of control over their situation and give some control by helping the person with dementia, the family care-giver and the staff.